Analysis of Contractor Performance On Stakeholder Satisfaction In Construction Expenditure Projects Rehabilitation of Malang City Using The PLS Method - Ardhiansyah, Widha; Teki Tjendani, Hanie; Witjaksana, Budi (Green Publisher Indonesia, 2023)
Contractors have a major role in the implementation of development projects. Therefore, it is necessary to evaluate the contractor's performance by related Stakeholders regarding the results and work processes carried out in order to meet Stakeholder satisfaction . This study aims to find the influence of contractor performance factors in the form of Quality Management, Environmental Management and Safety & Health Management on Stakeholder Satisfaction in the Malang City Rehabilitation Construction Expenditure Project. This research is a quantitative research with data collection methods in the form of interviews and questionnaires. The population of this research is Stakeholders in the Malang City Rehabilitation Construction Expenditure Project with a total sample of 45 people. The research data analysis technique uses the PLS SEM method. Research proves that Quality Management has no significant effect on Stakeholder satisfaction, while Environmental and Safety & Health management has a significant effect on Stakeholder satisfaction.